Basic methods of preparation of organic fertilizer from quail manure - Komar, Artem; Комар, Артем Станіславович; Комар, Артем Станиславович; Skliar, Oleksandr; Скляр, Олександр Григорович; Скляр, Александр Григорьевич; Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна (ТДАТУ, 2021)
By processing quail manure into organic fertilizer and using it in the soil, users and tenants of the land naturally restore humus, which in any case will bring profit in the form of an increase in yield.
Keywords: organic farming; depletion of the soil; volume of poultry breeding; quail; processing of poultry waste